"Picking up the crumbs of England": East African Asians in Yasmin Alibhai-Brown's autobiographies. (March 2018) - Hand, Felicity
Ugandan-born journalist, Yasmin Alibhai-Brown has published two autobiographical works: No Place like Home (1995) and The Settler's Cookbook: A Memoir of Love, Migration and Food (2008). The former is an account of her childhood and adolescence in Uganda up to the expulsion of the Asian community in 1972. The latter work is a highly unusual combination of autobiography combined with no less than 113 recipes, each of which highlights a specific person, period, or event in her memoir. While No Place Like Home responds to the accepted principles of autobiographical writing, The Settler's Cookbook defies generic classification and is perhaps the author's own way of depicting the Asian community, sandwiched between two communities, the Europeans and the Africans. In this article I propose to focus on Alibhai-Brown's critical stance towards her community in her analysis of the social and political reasons for the negative image of the Asian in East Africa, as reflected in the first part of my title. Despite her frank observations on the endogamic nature of her community, she also pays tribute to the many Asian women who tried to build bridges between communities, a difficult task considering the constraints placed on female agency. As she states in The Settler's Cookbook, "[t]o be an Asian woman in the 1950s in East Africa must have been both exhilarating and confusing" (2008: 151). Alibhai-Brown's work, written in the diaspora and with the benefit of hindsight, has unravelled many of the paradoxes of the ambiguous position of the South Asian community in East Africa.